Generation of a human SLC12A3 knock-in human induced pluripotent stem cell line (CMCi014-A-82) using CRISPR-Cas9 system - Sun Woo Lim; Kang In Lee; Sheng Cui; Xianying Fang; Yoo Jin Shin; Hanbi Lee; Chul Woo Yang; Jae Young Lee; Byung Ha Chung (Stem Cell Research)
Gitelman’s disease is caused by a genetic mutation in the solute carrier family 12 member 3 (SLC12A3) gene, which encodes the sodium chloride cotransporter. In this study, we generated a stable human induced pluripotent stem cell (hiPSC) line, WTC11-SLC12A3 (CMCi014-A-82), by knocking in the entire SLC12A3 gene at the SHS231 locus in healthy wild-type control hiPSCs (WTC11). We verified that WTC11-SLC12A3 expressed pluripotency markers and exhibited normal stem cell morphology. Furthermore, this cell line maintains a normal karyotype and can differentiate into the three germ layers. Therefore, this cell line may provide a basis for gene therapy for Gitelman’s disease.